Long-term outcome in children with nutritional vitamin B12 deficiency - Melike Sezgin Evim; Şahin Erdöl; Özlem Özdemir; Birol Baytan; Adalet Meral Güneş (Turkish Journal of Hematology, 2011)
Objective: Vitamin B12 deficiency is frequently observed in developing countries. Herein we report the long-term clinical and laboratory outcomes in 45 children presented with various symptoms of vitamin B12 deficiency.Materials and Methods: Symptoms and physical findings, and percentiles for weight, height, and head circumference at presentation were recorded. The educational level of the patients’ mothers, vitamin B12 deficiency-related diseases and family income data were collected. Complete blood count, serum vitamin B12, folate, iron, iron binding capacity and ferritin, and plasma homocysteine levels were recorded measured at presentation. The patients were treated with vitamin B12, as follows: 1 mg/d IM for 1 week, followed by 1 mg IM QWK for 2 weeks, and then monthly 1mg injections. Patients were neurologically and hematologically re-evaluated after treatment. The visual evoked potential (VEP) test was used to examine the integrity and function of the visual pathway. Brainstem evoked potential (BAEP) responses were used to analyze auditory function. Neuromotor development was assessed using Denver II Development Screening Test. Results: The mean age of 20 male and 25 female patients was 5.6±5.9 years (range: 1.4 months-17 years). The most common symptoms at presentation were weakness, failure to thrive, and hematologic manifestations (pallor, petechiae, ecchymosis). Abnormal neurologic findings at presentation were observed in 20% of the patients, and were more commonly observed in those <2 years. VEP, BAEP, and Denver II Development tests were performed in 66% of the patients one year after vitamin B12 replacement was started. VEP and BAEP interval prolongation was observed in 37% and 17% of the cases, respectively. Denver II Development Test results showed developmental delay in 20% of the patients tested.Conclusion: All the patients achieved full hematologic recovery within 1 month of treatment onset. Neurological symptoms resolved following B12 administration; however, during long-term follow-up ranged from 17% to 37% of the tested patients had persistent VEP; BERA, and Denver II abnormalities. Neurological symptoms resolved following B12 administration; however, during long-term follow-up 33% of the patients had persistent VEP, BERA, and Denver II abnormalities. As such, clinicians should continue to follow-up such patients even after hematologic and clinical improvement are obtained in order to assess their neurologic status.